A Chemometric Strategy in the Development of a RP-UPLC Method for the Quantitative Resolution of a Two-Component Syrup Formulation. (12th February 2022) - Rouhani, Ghazal; Ertekin, Zehra Ceren; Dinç, Erdal
Abstract: A novel chemometric strategy was implemented in the development of a new ultraperformance liquid chromatography method for the quantitative estimation of guaifenesin and pseudoephedrine hydrochloride in a two-component syrup formulation with minimal experimental effort, time and reagent. A full factorial design with three factors was investigated to find optimal working conditions of chromatographic factors (column temperature, flow rate, and 0.1 M H3 PO4 % in mobile phase) that affect the chromatographic separation. Then, optimum experimental conditions providing adequate separation of the analyzed drug substances within the short runtime were determined. Under optimal experimental conditions, the retention times for guaifenesin and pseudoephedrine hydrochloride were obtained as 0.817 and 1.430 min, respectively. In the optimized RP-UPLC method, chromatographic response was reported as a linear function of concentration between 5.0 and 80.0 μg/mL for guaifenesin and 10.0–90.0 μg/mL for pseudoephedrine hydrochloride. The proposed method was carefully validated and successfully applied to quality control and analysis of a cough syrup preparation containing guaifenesin and pseudoephedrine hydrochloride. Consequently, the proposed reversed-phase ultraperformance liquid chromatography method provided an opportunity to quantify relevant drugs with small amount of reagents and short runtime.